Pace strategy in the 1500m swimming in Tokyo 2021 - Russomanno, T. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The ideal pace strategy (PS) in competitive long-distance swimming is not widely known in the literature but in generally is represented by U-shaped curve(Lara and Del Coso, 2021), indicating that professional long-distance swimmers have a fast pace in the first 100m and again another fast pace in the final meters of the race, while most of the entire race they keep the speed constant with small fluctuations. Nevertheless, there is no agreement on how the pace strategy determines the winners in a 1500 m competition, thus, the aim of this study is to analyze the performance of Olympic Games finalists in the mens 1500-meter freestyle race over the last Olympic games in Tokyo 2021 and identify the pace strategy most used by the best swimmers in the 1500 m. METHODS: The sample of the study was collected from public data files available at FINA (Fédération Internationale De Natation) website(www.fina.org). Lap times (every 50 m) of the athletes (n = 8) finalists of the Olympic Games Tokyo 2021 were used in this study. To evaluate the athletes pace strategies, descriptive statistical analysis of the laps was done (mean, standard deviation, coefficient of variation) together with boxplots of the laps. T-test evaluate the difference from the first third of the race to the second and final third of the race (500m splits), Wilcoxon-Signed Ranks test was performed when the data did not present a normal distribution. The times at each 250 m were also compared with the following split times (250, 500, 750,1000,1250, and 1500 m), to assess which sections of the race were statistically different. The Friedman test with Bonferroni post hoc correction was used for p < 0.003. These tests were run on SPSS 27 software. RESULTS: The results found were a parabolic race strategy (U-shaped) performed by all athletes, where the partial velocities as a function of time show an acceleration at the beginning of the race (250 m) followed by a maintenance of the speed in the middle part of the race (250 to 1250 m) and finally an increase in their accelerations in the final part of the race (1250 to 1500 m) characterizing a final sprint. CONCLUSION: From the data analyzed it was identified U-shaped curve pace strategy profile used by all the athletes analyzed in this study. Most likely the fast pace in the beginning is related to the use of starting Blocks (diving start). A plausible explanation for athletes to assume a slower rhythm after some meters is related to a model of tele-anticipation, where the swimmer wants to save energy so that afterwards a final sprint can be performed. From the practical aspect the U-shape PS is the best strategy so far (as we know) and should be used in training to improve performance of young athletes. Some limitations of the study, only finalist were analyzed, so maybe different PS can be adopted in other heats before the finals. Stroke rate and stroke length was not measured, this may help to understand whats within the PS in long distance events.